2015
DOI: 10.3892/mmr.2015.4154
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fluorescent NBD-cholesterol efflux in THP-1-derived macrophages

Abstract: Abstract. Macrophage cholesterol efflux is important in maintaining cellular lipid homeostasis and preventing the formation of lipid-laden foam cells. Although radioactive [ 3 H]-cholesterol is widely used as a tracer in cholesterol efflux assays, the lengthy and labor-intensive assay procedure, and the radioactivity disposal procedure limit the use of this assay for high-throughput screening. In the present study, a novel procedure using fluorescent N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl) amino)-23,24-bisnor-5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In vitro generation of PMA‐induced monocytes to macrophage differentiation showed well‐established molecular characteristics of mature macrophages such as decreased rate of proliferation, increased adherence, improved phagocytosis, and expression of scavenger receptors . Macrophages present in the atherosclerotic plaque give rise to a special type of cells which could ingest OxLDL and become overloaded with lipids called foam cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro generation of PMA‐induced monocytes to macrophage differentiation showed well‐established molecular characteristics of mature macrophages such as decreased rate of proliferation, increased adherence, improved phagocytosis, and expression of scavenger receptors . Macrophages present in the atherosclerotic plaque give rise to a special type of cells which could ingest OxLDL and become overloaded with lipids called foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro generation of PMA-induced monocytes to macrophage differentiation showed well-established molecular characteristics of mature macrophages such as decreased rate of proliferation, increased adherence, improved phagocytosis, and expression of scavenger receptors. 17 Macrophages present in the atherosclerotic plaque give rise to a special type of cells which could ingest OxLDL and become overloaded with lipids called foam cells. This study also showed the transdifferentiation of PMA derived macrophages into foam cells with the increased expression of upregulated scavenger receptors: SR-A1, SR-B1, and LOX-1 and with the reduced expression of transporter proteins ABCA1/ABCG1.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol efflux was measured using the methods modified from Song et al . In brief, THP‐1 macrophages were equilibrated with NBD cholesterol (5 μmol/L) for 4 hours.…”
Section: Methodsmentioning
confidence: 99%
“…As previously described, differentiated THP‐1 cells were equilibrated with NBD cholesterol {22‐[ N ‐(7‐nitrobenz‐2‐oxa‐1,3‐diazol‐4‐yl)amino]‐23,24‐bisnor‐5‐cholen‐3β‐Ol; Thermo Fisher Scientific} for 18 h, then washed with PBS and treated with rHSP‐27 overnight (26). Thereafter, cells were incubated with the extracellular cholesterol acceptors, ApoA1 (15 mg/ml; Cedarlane) or HDL (50 mg/ml HDL; Cedarlane) in serum‐free medium for 6 h. The fluorescence‐labeled cholesterol released from cells into the medium was measured with a microplate reader at excitation l = 485 nm and emission l = 535 nm.…”
Section: Gm‐csf Elisamentioning
confidence: 99%